The brightest of dreams - Mason, Susan Anne (Mason, Susan Anne. Canadian crossings, 2020)
"Determined to keep his family together, Quinten travels to Canada to find his siblings and track down his employer's niece who ran off with a Canadian soldier. When Quinten rescues her from a bad situation, Julia is compelled to repay him by helping him find his sister--but soon after, she receives devastating news that changes everything." -- Publisher annotation.